2012
DOI: 10.1128/iai.00081-12
|View full text |Cite
|
Sign up to set email alerts
|

Mutations That Impact the Enteropathogenic Escherichia coli Cpx Envelope Stress Response Attenuate Virulence in Galleria mellonella

Abstract: ABSTRACTIn this paper, we show that the larvae of the greater wax moth,Galleria mellonella, can be used as a model to study enteropathogenicEscherichia coli(EPEC) virulence. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
56
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 76 publications
6
56
1
1
Order By: Relevance
“…In EPEC, CpxRA is required to adapt to envelope stress; however, CpxRA activation leads to decreased TTS gene expression; these apparently contrasting roles suggest that cpxRA expression is under tight control in vivo (13). In support of this, it was previously shown that both inhibition and constitutive activation of CpxRA in EPEC negatively affect virulence in the wax worm larva model (30). Consistent with these data, attempts to complement the C. rodentium CpxRA TCS by using low-copy-number plasmids were successful in vitro but resulted in only inconsistent complementation in vivo, further suggesting that fine-tuning of cpxRA expression is important for infection (data not shown).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In EPEC, CpxRA is required to adapt to envelope stress; however, CpxRA activation leads to decreased TTS gene expression; these apparently contrasting roles suggest that cpxRA expression is under tight control in vivo (13). In support of this, it was previously shown that both inhibition and constitutive activation of CpxRA in EPEC negatively affect virulence in the wax worm larva model (30). Consistent with these data, attempts to complement the C. rodentium CpxRA TCS by using low-copy-number plasmids were successful in vitro but resulted in only inconsistent complementation in vivo, further suggesting that fine-tuning of cpxRA expression is important for infection (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, the constitutive activation of CpxRA negatively impacts virulence gene expression in vitro. In addition to these findings, the deletion of cpxR and subsequent inactivation of CpxRA leads to decreases in cell adherence and in vitro infectivity of EPEC (30). These studies provide compelling evidence that CpxRA is involved in the regulation of essential colonization and virulence factors of EPEC and that the activation of this TCS must be carefully fine-tuned to protect cells against cell envelope stress while allowing for virulence gene expression.…”
mentioning
confidence: 92%
“…The similarity of these results to the Cpx data, along with the inclusion of the ToxRregulated ompT in the list of CpxR-responsive genes, suggests that attenuation of CT and TCP production in the RND-deficient strain may be due to the activation of the Cpx system. Although the Cpx system has been linked to virulence in other pathogens (68)(69)(70)(71)(72)(73), our data indicate that the Cpx system does not affect V. cholerae virulence factor production. This was evidenced by the fact that cpxR deletion, constitutive activation of the Cpx system (i.e., cpxA*), or chemical activation of the Cpx system (i.e., with CuCl 2 ) did not affect CT or TCP production.…”
Section: Discussionmentioning
confidence: 72%
“…(46,47), Legionella pneumophila (31,48), Shigella spp. (33)(34)(35), enteropathogenic E. coli (32,49,50), Actinobacillus suis (51), Haemophilus ducreyi (52,53), Xenorhabdus nematophila (37,54), and Yersinia pseudotuberculosis (55)(56)(57). However, direct evidence that the Cpx system can affect pathogen fitness and virulence in vivo within an animal host is limited to only a few studies (47,50,53,54).…”
mentioning
confidence: 99%
“…(33)(34)(35), enteropathogenic E. coli (32,49,50), Actinobacillus suis (51), Haemophilus ducreyi (52,53), Xenorhabdus nematophila (37,54), and Yersinia pseudotuberculosis (55)(56)(57). However, direct evidence that the Cpx system can affect pathogen fitness and virulence in vivo within an animal host is limited to only a few studies (47,50,53,54). In UPEC, the Cpx system has been examined primarily with respect to its ability to modulate the expression of P pili, filamentous adhesive organelles that can promote bacterial interactions with host kidney cells (27,28,58).…”
mentioning
confidence: 99%